Cerminan Cerminan Tuntutan Sosial Terhadap Perempuan Pada Cerpen Tulungin Tiang Meme! Karya Ni Wayan Antari - Murwa Kuncara, I Made Sangging; Antara, I Gde Nala; Putra, Ida Bagus Rai (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This research analyzed identify and describe the reflection of social demands that occur to women in the short story Tulungin Tiang Meme! This short story is analyzed using a feminist approach. To facilitate the analysis process, certain methods and techniques are needed. This study consists of three stages, the first is the data provision stage, which is carried out using the observation method, supported by note-taking and translation techniques, the second is the data analysis stage, applying qualitative methods with the help of analytical descriptive techniques and the third is the stage of presenting the results of the analysis, using informal methods with the support of inductive and deductive techniques. The feminist analysis in this study will include how the treatment received by a woman and her demands in the social environment of society are depicted through literary works. The results of the study show that through the depiction of the main character's inner conflict, short story shows that women are often not only victims of patriarchal social structures, but are also required to continue to sacrifice and adapt in order to maintain family harmony. The reflects how cultural values and social constructions still greatly influence women's lives, even to the point of touching on very personal aspects of life choices.